2013
DOI: 10.1590/s0104-11692013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Professional nursing practice: environment and emotional exhaustion among intensive care nurses

Abstract: the mediating role of emotional exhaustion may negatively influence care delivery. Therefore, there is a need to adopt strategies to minimize this condition among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
84
7
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 21 publications
21
84
7
24
Order By: Relevance
“…The prominent and consistent behavior of this Burnout aspect found in this and other studies (8,10) probably indicates its nuclear role in relation to the other domains of the syndrome. It is worth mentioning that depersonalization has been considered a behavioral defense mechanism against emotional exhaustion and reduced personal accomplishment, as another consequence of Burnout (3) .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The prominent and consistent behavior of this Burnout aspect found in this and other studies (8,10) probably indicates its nuclear role in relation to the other domains of the syndrome. It is worth mentioning that depersonalization has been considered a behavioral defense mechanism against emotional exhaustion and reduced personal accomplishment, as another consequence of Burnout (3) .…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the work environment, this study found values close to 2 in all NWI-R subscales, results similar to Brazilian investigations carried out in Intensive Care Units (8,12,15) and better than those observed in a study carried out in Primary Care Units (16) .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations